Chemical analysis of Cyproheptadine Hydrochloride in appetite-stimulating herbs marketed in Banyumas regency: ensuring consumer safety - Indarwati, Atika; Fitriana, Adita Silvia; Rahmawati, Nur (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Jamu, a traditional Indonesian herbal medicine, is widely used in traditional healing practices nationwide, including the Banyumas Regency. The Indonesian government has implemented restrictions that forbid the inclusion of medicinal compounds in jamu, as their unregulated usage poses possible health hazards. Cyproheptadine hydrochloride is a frequently encountered medicinal component in appetite-stimulating herbs. However, the extent of adulteration of cyproheptadine hydrochloride in appetite-stimulating herbs marketed in Banyumas Regency is undisclosed. This study purposed to analyze and quantify the presence of cyproheptadine hydrochloride in appetite-stimulating herbs that are available for sale in the Banyumas Regency. The aim was to inform customers about these herbs' possible pharmaceutical ingredient content. The study utilized a qualitative analysis of thin-layer chromatography (TLC) and a quantitative analysis with a UV-Vis spectrophotometer. Fourteen samples of appetite-stimulating herbs in powdered, capsule, and tablet forms were gathered from different areas within the Banyumas Regency. Qualitative analysis revealed cyproheptadine hydrochloride in two herbal samples, SNM TG and SNM AM. The quantitative examination revealed that the content of cyproheptadine hydrochloride in SNM TG was 10.92 mg/5g, whereas in SNM AM, it was 7.93 mg/5g. These findings indicate that there have been breaches of regulations, and individuals who ingest these herbs may be susceptible to health problems. Further investigation is required to analyze a broader range of appetite-stimulating herbal samples, particularly those in liquid form, to ascertain the level of contamination with cyproheptadine hydrochloride and provide essential data for health regulations.